2007
DOI: 10.1007/s00267-006-0296-5
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impacts of Zebra Mussels on Drinking Water Treatment and Electric Power Generation Facilities

Abstract: Invasions of nonnative species such as zebra mussels can have both ecological and economic consequences. The economic impacts of zebra mussels have not been examined in detail since the mid-1990s. The purpose of this study was to quantify the annual and cumulative economic impact of zebra mussels on surface water-dependent drinking water treatment and electric power generation facilities (where previous research indicated the greatest impacts). The study time frame was from the first full year after discovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(85 citation statements)
references
References 11 publications
1
84
0
Order By: Relevance
“…Rising water temperatures may lead to replacement of coldwater mollusc species by more thermophilic ones (Daufresne et al 2004), but the mechanisms that may explain this shift are not yet understood. As molluscs constitute a large share of the group of macroinvertebrate invaders (Karatayev et al 2009;Leuven et al 2009) and invasive, fouling molluscs have serious economic and ecological impacts (Connelly et al 2007;Pimentel et al 2005;Strayer 2010;Vanderploeg et al 2002), there is a particular need for knowledge on physiological tolerances of these species. Knowledge on facilitating or limiting factors for the establishment of non-native mollusc species could be helpful to predict future species replacements and to derive management options for invasive species.…”
Section: Introductionmentioning
confidence: 99%
“…Rising water temperatures may lead to replacement of coldwater mollusc species by more thermophilic ones (Daufresne et al 2004), but the mechanisms that may explain this shift are not yet understood. As molluscs constitute a large share of the group of macroinvertebrate invaders (Karatayev et al 2009;Leuven et al 2009) and invasive, fouling molluscs have serious economic and ecological impacts (Connelly et al 2007;Pimentel et al 2005;Strayer 2010;Vanderploeg et al 2002), there is a particular need for knowledge on physiological tolerances of these species. Knowledge on facilitating or limiting factors for the establishment of non-native mollusc species could be helpful to predict future species replacements and to derive management options for invasive species.…”
Section: Introductionmentioning
confidence: 99%
“…Both of these mussel populations expand rapidly causing serious economic and ecological effects. Facilities that rely on water intake, such as dams, become clogged with these invasive mussel species, which leads to the need for removal strategies, with large economic cost (Connelly et al 2007). In addition to the monetary cost, they also cause major ecological effects by significantly reducing the biomass and production of edible primary producers.…”
Section: Managing Against Novel Ecosystemsmentioning
confidence: 99%
“…Economic impacts of zebra mussels have not been examined in detail since the mid1990s, although predictions have ranged as high as $1 billion per year (Connelly et al, 2007;Pimentel, 2005). Moreover, the over-land transportation of boats, motors, and trailers poses one of the greatest risks for spreading zebra mussels as larger mussels can live out of water for up to three days.…”
Section: Zebra Mussels As a Terrorist Threatmentioning
confidence: 99%
“…Ecologists speculate the mussels will continue to spread into additional rivers and inland lakes that are currently uninfected but within range of the invasion based on environmental and geological variables. Connelly et al (2007) surveyed water treatment facilities within known zebra mussel range and reported that respondents thought zebra mussels had been in the facility for 6 months to 1 year before discovery; only 20% of responding facilities had preventative measures in place prior to the discovery of zebra mussels. Given the ecological and human dimensions of zebra mussel invasions and management, it is possible that zebra mussels appeared in the case study lake as part of the "natural" ecological invasion of mussels through the Midwest and that the officials were not aware of the mussel invasion because, like Connelly et al (2007) found, they were not actively looking for them.…”
Section: Zebra Mussels As a Terrorist Threatmentioning
confidence: 99%